Metagenomic next-generation sequencing identifies native valve Aspergillus fumigatus endocarditis with cerebral involvement: a case report - Wu, Weibing; Xu, Jingjing; Ruan, Jianling; Tian, Baoping; Xuan, Nanxia (Frontiers in Cardiovascular Medicine, 2025)
Aspergillus endocarditis is a rare but highly fatal condition, particularly in immunocompromised patients. This case report describes a 74-year-old male with native valve Aspergillus fumigatus endocarditis and intracranial infection. Diagnosis was complicated by atypical presentation and negative blood cultures, but metagenomic next-generation sequencing (mNGS) enabled rapid identification of the pathogen. This case is notable for being the first to document Aspergillus fumigatus endocarditis with cerebral involvement confirmed by mNGS, highlighting the importance of early diagnosis and advanced diagnostic tools in improving outcomes.